Disruption management in a two-period three-tier electronics supply chain - Johannes Danusantoso; Scott A. Moses (Cogent Business & Management, 2016)
We study strategies to manage demand disruptions in a three-tier electronics supply chain consisting of an Electronics Manufacturing Services provider, an Original Equipment Manufacturer (OEM), and a Retailer. We model price sensitivity of consumer demand with the two functions commonly used for this purpose, linear and exponential, and introduce disruptions in the demand function. We assume each supply chain member faces an increasing marginal unit cost function. Our decentralized supply chain setting is governed by a wholesale price contract. The OEM possesses greater bargaining power and therefore is the Stackelberg leader. A penalty cost incurred by the Retailer is introduced to capture the cost of deviation from the original plan. We find exact analytical solutions of the effectiveness of managing the disruption when the consumer demand function is linear, and we provide numerical examples as an illustration when the consumer demand function is either linear or exponential. We show that the original production quantity exhibits some robustness under disruptions in both centralized and decentralized supply chains, while the original optimal pricing does not. We show that supply chain managers should not automatically react to an individual disruption, in certain cases it is best to leave the production plan unchanged.
Keywords: 650